Development Of Contextual Accounting Learning Assessment Based On Lesson Study In High School - Adiningsih, Sri Hutami; Pratama, Is Arianto; Syam, Andi Zulitsnayarti Mardhani; Damasinta, Alfiana (Amirul Bangun Bangsa Publishing, 2025)
This research aims to analyze and describe the implementation of accounting learning assessments by secondary school teachers in Mamuju City, West Sulawesi, as well as developing contextual assessment-based lesson studies. The research uses a research and development (R&D) approach with the subject of junior high school accounting teachers. Data was collected through interviews, observation and documentation, then analyzed using an interactive analysis model which includes data collection, reduction, presentation and verification. The validity of the data was tested through triangulation of methods and sources. The results show that the assessment includes affective, cognitive and psychomotor aspects. Affective assessment includes spiritual and social attitudes, each of which uses self-assessment techniques as well as observation, reflection journals, and peer assessment. Cognitive assessment is carried out through tests and assignments, while psychomotor assessment involves projects, performance and portfolios. Development was carried out on assessment instruments for these three aspects, including improvements to techniques, instruments, and timing of assessment implementation.